Предмет: Алгебра, автор: EugeniaRyskova

ПОМОГИТЕ С АЛГЕБРОЙ
АаааааааааААААААаааАааааааААААаа
ЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫЫ

Приложения:

Ответы

Автор ответа: kucherjavuy
1

Ответ:

x1*x2+x1*+x2=-3

(x1+x2)^2+2*x1*x2=9

Объяснение:

x^2-5x-4=0

\sqrt{D}=5^2-4*1*(-4)

\sqrt{D}=25+16=41

D=\sqrt{41}

x1 =\frac{5-\sqrt{41} }{2}

x2=\frac{5+\sqrt{41} }{2}

x1*x2+x1*+x2=-3

\frac{5-\sqrt{41} }{2} *\frac{5+\sqrt{41} }{2}+\frac{5-\sqrt{41} }{2}+\frac{5+\sqrt{41} }{2}=\frac{(5^{2}-\sqrt{41} ^{2})  }{2} +\frac{10}{2}=\frac{25-41}{2}+5=-8+5=-3

(x1+x2)^2+2*x1*x2=9

(\frac{5-\sqrt{41} }{2}+\frac{5+\sqrt{41} }{2})^{2}+ 2*\frac{5-\sqrt{41} }{2} *\frac{5+\sqrt{41} }{2}=\frac{(5^{2}-\sqrt{41} ^{2})  }{2} =(\frac{10}{2})^2 +2*\frac{25-41}{2}=25-16=9

Похожие вопросы